2020
DOI: 10.1002/fsn3.1946
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Macro and Nano‐emulsions of cinnamon essential oil on the properties of edible active films

Abstract: Over the last few years, the tendency to use biodegradable polymers in food packaging has grown due to increased awareness regarding ecological and environmental problems and contamination of natural resources caused by nondegradable petrochemical-based polymers (Al-Tayyar et al., 2020; da Silva Filipini et al., 2020). Considering this, two types of biodegradable polymers have been investigated: edible and nonedible biopolymers. Carbohydrates and proteins or their combination with lipids are usually used for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 53 publications
(105 reference statements)
0
22
0
Order By: Relevance
“…Nevertheless, the films formed by it have poor mechanical and barrier properties. The combination of decomposable polymers with different properties and structures seems to be an appropriate solution to overcoming these shortcomings (Cazón et al., 2018 ; Fattahi et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the films formed by it have poor mechanical and barrier properties. The combination of decomposable polymers with different properties and structures seems to be an appropriate solution to overcoming these shortcomings (Cazón et al., 2018 ; Fattahi et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was reported that adding α-tocopherol nanocapsules reduced the TS and EM of carboxymethyl cellulose films [75]. Fattahi, Ghanbarzadeh [76] reported that incorporating a cinnamon oil nanoemulsion into a carboxymethyl cellulose reduced the TS and increased the EB. Aziz and Almasi [77] reported that incorporating thyme extract nanoliposomes (0, 5, 10, or 15% wt.)…”
Section: Mechanical Propertiesmentioning
confidence: 98%
“…Lecithin-based nanocapsules have been reported to result in softer materials with lower TS by causing discontinuities in the biopolymer films. Fattahi and Ghanbarzadeh [84] reported that incorporating a cinnamon oil nanoemulsion into a carboxymethyl cellulose matrix reduced the TS and increased the EB of the films. Incorporating essential oils probably weakened the network structure through interruption of the intermolecular interactions between the biopolymer molecules.…”
Section: Mechanical Propertiesmentioning
confidence: 99%